Synthesis of textured films of hexagonal barium ferrite on Al2O3/Si3N4 amorphous structure. Issue 1 (November 2021) - Mironovich, A. Yu.; Kostishyn, V.G.; Isaev, I.M.
Abstract: In this work structural studies of BaFe12 O19 /Al2 O3 /Si3 N4 thin films with different thicknesses of aluminum oxide and silicon nitride are represented. It is shown that barium hexaferrite crystallizes on the amorphous surface of aluminum oxide with spontaneously formed (00l) uniaxial texture. Microstructural differences in BaFe12 O19 films were observed with varying of the thickness of amorphous sublayers, which is explained by the effect of mechanical stress.